2016
DOI: 10.1021/jacs.5b13275
|View full text |Cite
|
Sign up to set email alerts
|

Cinchona Alkaloid-Catalyzed Asymmetric Conjugate Additions: The Bifunctional Brønsted Acid–Hydrogen Bonding Model

Abstract: Wynberg's report from 1977 that natural cinchona alkaloids catalyze the asymmetric conjugate addition of aromatic thiols to cycloalkenones is a landmark discovery in hydrogen bonding organocatalysis. Wynberg proposed that this reaction proceeded via the formation of a thiolate-alkylammonium tight ion pair and activation of the enone electrophile by a hydrogen bond from the catalyst's hydroxyl group. This reaction model provided the mechanistic basis for understanding Wynberg's reaction and many other asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…The structures observed in the most favorable TS‐I systems indicate that electrophile 1 g interacts with the protonated quinuclidine group of the quinine catalyst before the nucleophilic attack of the nitronate takes place (Figure A). This model has been suggested previously by Houk and co‐workers for other chemical transformations catalyzed by cinchona alkaloids, and a mechanism with similar interaction mode has been proposed by Paton and co‐workers in the Henry reaction of aldehydes catalyzed by chiral phosphazenes . In contrast, all TS‐I steps in which the electrophile is interacting with the OH group of the catalyst show considerably higher energies (Figure B)…”
Section: Resultssupporting
confidence: 79%
“…The structures observed in the most favorable TS‐I systems indicate that electrophile 1 g interacts with the protonated quinuclidine group of the quinine catalyst before the nucleophilic attack of the nitronate takes place (Figure A). This model has been suggested previously by Houk and co‐workers for other chemical transformations catalyzed by cinchona alkaloids, and a mechanism with similar interaction mode has been proposed by Paton and co‐workers in the Henry reaction of aldehydes catalyzed by chiral phosphazenes . In contrast, all TS‐I steps in which the electrophile is interacting with the OH group of the catalyst show considerably higher energies (Figure B)…”
Section: Resultssupporting
confidence: 79%
“…A broad range of nitroolens 2a-g with different b-aryl substituents all gave the desired syn-5a-g in 73-85% yield and with 7 : 1 to 10 : 1 dr values, with 93-96% ee (entries 1-7, Table 2). b-Alkenyl nitroolens 2h-l furnished adducts syn-5h-l in >12 : 1 dr and 92-94% ee (entries [8][9][10][11][12]. Differently substituted a-azido indanones 1b-e also worked well to give syn-5m-p with high dr and ee values (entries 13-16).…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…10 For bifunctional tertiary amine catalysis, theoretical studies have proposed three types of working models that differ in how H-bond donors of the catalysts interact with the nucleophile and electrophile (Scheme 1A). [11][12][13][14][15] The ion pair-hydrogen bonding model (type A) was initially proposed by Wynberg 11a and supported by theoretical studies by Cucinotta and Gervasio. 11b The Brønsted acidhydrogen bonding model (type B) was revealed by Houk et al via quantum mechanical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1977, Wynberg and co-workers [209] reported that cinchona alkaloids catalyze the asymmetric conjugate addition of aromatic thiols to cycloalkenones (Scheme 32) [210]. Quantum mechanical calculations proposed transition state of type 63 for these reactions [211]. and the conjugate acids 63 of the corresponding formates.…”
Section: Catalysis Of 14-(conjugate) Additionsmentioning
confidence: 99%